Connecting With Fundamental Mathematical Knowledge Directly: The Organizational Features of Good Mathematical Cognitive Structure - Yang, Zezhong; Zhang, Yanqing; Wang, Kai; Zhu, Ming (Frontiers in Psychology, 2018)
This paper reported a study of good mathematical cognitive structure (GMCS) based on the 43 top university students as participants and the 82 concepts of Calculus as materials with the method of social network analysis. The results indicated the GMCS has the organizational features as follows: (1) the mathematical knowledge (MK) in GMCS interconnected widely, especially that MK with the higher connection tightness; (2) most connections between MK were direct; (3) the MK of the basic and higher inclusive level owned the greater impact; (4) There were multiple MK as accumulation points connecting others to form some subsets. These new finding enriched the results of the studies on GMCS and promoted the exploration on the GMCS. In the view of this, the proposals we put forward for teachers is they should pay attention to the basic and abstract MK and help their students construct many direct connections between the MK in their mind.